GPS and GNSS for land surveyors - Van Sickle, Jan (CRC Press, 2024)
"Based on the success of the previous four editions, this new edition includes Global Navigation Satellite Systems (GNSS) in the title, of which GPS is part. Neither simplistic nor overly technical, the new edition is updated with the changes in GPS and GNSS hardware, software, and procedures. It describes why modern GNSS positions can be acquired with more certainty, with increased stability, and improved tracking in obstructed areas. The book offers a rare combination of knowledge and skills that every land surveyor needs to master. Intended for both ingenues and professionals in the field, broad concepts are explained in an accessible way."